2016
DOI: 10.1016/j.cattod.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Fischer–Tropsch synthesis product selectivity over an industrial iron-based catalyst: Effect of process conditions

Abstract: Please cite this article in press as: B. Todic, et al., Fischer-Tropsch synthesis product selectivity over an industrial iron-based catalyst: Effect of process conditions, Catal. Today (2015), http://dx. a b s t r a c tThe effect of process conditions on product selectivity of Fischer-Tropsch synthesis (FTS) over industrial iron-based catalyst (100 Fe/5 Cu/4.2 K/25 SiO 2 ) was studied in a 1-L stirred tank slurry reactor. Experiments were performed over a range of different reaction conditions, including three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 52 publications
(87 reference statements)
1
72
0
1
Order By: Relevance
“…They have also reported that these interactions have great influence on the catalytic activity in the studied reaction. Todic et al [20] reported, that the increase of the reaction temperature and ratio between CO and H 2 increase the selectivity to methane production and leads to decrease towards C 5? production.…”
Section: Resultsmentioning
confidence: 99%
“…They have also reported that these interactions have great influence on the catalytic activity in the studied reaction. Todic et al [20] reported, that the increase of the reaction temperature and ratio between CO and H 2 increase the selectivity to methane production and leads to decrease towards C 5? production.…”
Section: Resultsmentioning
confidence: 99%
“…The pilot test results showed that the iron based catalysts which acclimatized to the radio of 1.5 is favorable, so in this paper, H2/CO ratio of the shifted syngas is assumed to be 1.5. Based on the researches of catalysts performance in FT synthesis, Fe based catalyst and slurry reactors are employed for this study [37,38]. In FT synthesis, CO and H2 react exothermically in the presence of the catalysts to produce hydrocarbons, ranging from methane to high molecular weight wax (>Cn42).…”
Section: E Fischer-tropsch Synthesismentioning
confidence: 99%
“…Natural resources, such as coal, natural gas and biomass, can be converted into liquid hydrocarbon fuels via the Fischer-Tropsch synthesis (FTS) reaction [2]. Reactants (CO + H2) through this reaction are converted to an array of long chain molecules, mainly consisting of nparaffins and 1-and 2-olefins:…”
Section: Introductionmentioning
confidence: 99%